Moniliophthora perniciosa, the Causal Agent of Cacao Witches’ Broom Disease Is Killed in vitro by Saccharomyces cerevisiae and Wickerhamomyces anomalus Yeasts - Ferraz, Pedro; Brandão, Rogelio Lopes; Cássio, Fernanda; Lucas, Cândida (Frontiers in Microbiology, 2021)
Cacao plantations from South America have been afflicted with the severe fungal disease known as Witches’ Broom Disease, caused by the basidiomycete Moniliophthora perniciosa. Yeasts are increasingly recognised as good fungal biocides, although their application is still mostly restricted to the post-harvest control of plant and fruit decay. Their possible utilization in the field, in a pre-harvest phase, is nevertheless promising, particularly if the strains are locally adapted and evolved, and if they belong to species considered safe for man and the environment. In this work, a group of yeast strains originating from sugar cane-based fermentative processes in Brazil, the cacao-producing country where the disease is most severe, were tested for their ability to antagonize M. perniciosa in vitro. Wickerhamomyces anomalus LBCM1105 and Saccharomyces cerevisiae strains LBCM1112 from spontaneous fermentations used to produce cachaça, and PE2 widely used in Brazil in the industrial production of bioethanol, efficiently antagonized six strains of M. perniciosa, originating from several South America countries. The two fastest-growing fungal strains, both originating from Brazil, were further used to assess the mechanisms underlying the yeasts' antagonism. Yeasts were able to inhibit fungal growth and kill the fungus at three different temperatures, under starvation, at different culture stages, or using an inoculum from old yeast cultures. Moreover, SEM analysis revealed that W. anomalus and S. cerevisiae PE2 cluster and adhere to the hyphae, push their surface and fuse to them, ultimately draining the cells. This behaviour concurs with that classified as necrotrophic parasitism/mycoparasitism. In particular, W. anomalus within the adhered clusters appear to be ligated to each other through roundish groups of fimbriae-like structures filled with bundles of microtubule-sized formations, which appear to close after cells detach, leaving a scar. SEM also revealed the formation of tube-like structures apparently connecting yeast to hypha. These evidences suggest W. anomalus cells form a network of yeast cells connecting with each other and with hyphae, supporting a possible cooperative collective killing and feeding strategy. The present results provide an initial step towards the formulation of a new eco-friendly and effective alternative for controlling cacao Witches’ Broom Disease using live yeast biocides.